ROLLING KAPAL PANCING TONDA DI KABUPATEN SINJAI ROLLING OF TROLLING LINER ON SINJAI REGENCY - Aulia Azhar Wahab; St. Aisjah Farhum; Faisal Amir (Fish Scientiae, 2017)
Trolling liner was a dominance used by fishermans in Sinjai Regency was made by traditional without planning before, so stability and sea keeping ability about sea condition was unknown. The research aimed to analyze the rolling motion of trolling liner in regular condition of beam seas. The research was a case study of trolling liner used by the fisherman in Sinjai.Geometry measurement vessel form was done to get a model of trolling liner and then make a redesign as a compared and then make a simulation using program Maxsurf v8.i. the result showed that the sample have a good stability. Higher rolling was 18,168 on high wave -0,1971 m and lower rolling was -18,168 on high wave 0,1971 m,while there design showed high errolling was14,102 on high wave -0,1970 m and lower rolling was -14,102 on high wave 0.1968 m.